Nanoliposomal irinotecan with fluorouracil for the treatment of advanced pancreatic cancer, a single institution experience - Glassman, Danielle C.; Palmaira, Randze L.; Covington, Christina M.; Desai, Avni M.; Ku, Geoffrey Y.; Li, Jia; Harding, James J.; Varghese, Anna M.; O’Reilly, Eileen M.; Yu, Kenneth H. (BMC cancer, 2018)
Background Effective treatment options for advanced pancreatic cancer are finite. NAPOLI-1, a phase III randomized trial, demonstrated the efficacy of nanoliposomal irinotecan with fluorouracil/leucovorin (nal-IRI + 5-FU/LV) for the treatment of advanced pancreatic cancer following progression on gemcitabine-based chemotherapy. There are limited additional data on the safety and efficacy of nal-IRI + 5-FU/LV following FDA approval in October 2015. We examined the post-approval safety and effectiveness of nal-IRI + 5-FU/LV in advanced pancreatic cancer patients receiving treatment at Memorial Sloan Kettering Cancer Center. Methods A retrospective chart review was conducted of all patients beginning treatment with nal-IRI + 5-FU/LV from October 2015 through June 2017. Using the electronic medical record and institutional database, information was extracted pertaining to demographics, performance status (ECOG), prior therapies, dose, duration of treatment, adverse events, progression free survival (PFS), overall survival (OS) and treatment response. Results Fifty six patients were identified. Median progression free survival (PFS) was 2.9 months and median overall survival (OS) was 5.3 months. Patients with prior disease progression on irinotecan experienced PFS and OS of 2.2 and 3.9 mo, respectively. Patients without prior irinotecan exposure experienced significantly longer PFS (4.8 mo, p = 0.02) and OS (7.7 mo, p = 0.002), as did patients who received prior irinotecan without disease progression (PFS, 5.7 mo, p = 0.04; OS, 9.0 mo, p = .04). Progression on prior irinotecan was associated with greater lines of prior advanced disease chemotherapy (2 vs 1). Dose reductions (DR) were most frequently due to fatigue (42%) and diarrhea (37%), but were not associated with worse outcomes. In fact, patients with ≥1 DR experienced longer PFS (5.4 v 2.6 mo, p = 0.035 ). Sequential therapy with nab-paclitaxel + gemcitabine (nab-P + Gem) followed by nal-IRI + 5-FU/LV ( n = 25) resulted in OS of 23.0 mo. Mutations in TP53 were associated with shorter PFS. Conclusions These data support the safety and efficacy of nal-IRI + 5-FU/LV, reinforcing results of NAPOLI-1. Patients without disease progression on prior irinotecan fared significantly better than patients with progression, when treated with nal-IRI + 5-FU/LV. Sequential therapy with nab-P + Gem followed by nal-IRI + 5-FU/LV demonstrates encouraging median OS. These findings provide guidance for patients most likely to benefit from nal-IRI + 5-FU/LV.